If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9y + -5 = 6y + 4 Reorder the terms: -5 + 9y = 6y + 4 Reorder the terms: -5 + 9y = 4 + 6y Solving -5 + 9y = 4 + 6y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-6y' to each side of the equation. -5 + 9y + -6y = 4 + 6y + -6y Combine like terms: 9y + -6y = 3y -5 + 3y = 4 + 6y + -6y Combine like terms: 6y + -6y = 0 -5 + 3y = 4 + 0 -5 + 3y = 4 Add '5' to each side of the equation. -5 + 5 + 3y = 4 + 5 Combine like terms: -5 + 5 = 0 0 + 3y = 4 + 5 3y = 4 + 5 Combine like terms: 4 + 5 = 9 3y = 9 Divide each side by '3'. y = 3 Simplifying y = 3
| 6(v+6)-5=1+6v | | -2(x)=8 | | 2x-3+x=63 | | 2(4-2)x(6+4)+8= | | 2w+3=8 | | -8c+6=-42 | | 2+4w-2w=34 | | -3x-12y=3 | | 2(2x)=18 | | 0.4*x^2+8x+40=-0.6*x^2+60 | | 5x=7+6x | | 1+(4+t)= | | 7x(1-x)=5x-10 | | 2(3+n)=5+n | | 7z-4z=2z-5-3z | | 6x-3=2y+8 | | 15x-1=11x-5 | | n^2-4n-4=-2.5 | | 3b-6=0 | | 4x+9y=-1 | | 5d+25=10b+5 | | 0=x^3+8x^2+20x+16 | | 10m+5=55 | | (6x-14)=14 | | X+1=-x+(-5) | | 3(7c-1)-12=19c+3 | | -3m+15.88-2.25=-17.48 | | 2+y=17-4y | | 6(2.3x-7)+(4x+11)= | | b+7=.5b+17 | | -11d+8=-13d-10 | | 9+(x+-9)= |